Hubungan Self Care Dan Sedentary Lifestyle Dengan Prevalensi Penyakit Jantung Koroner Di Rumah Sakit Umum Daerah dr. Zainoel Abidin Banda Aceh - Irna Silvia al Amna; Teuku Samsul Bahri; Ahyana (Sekolah Tinggi Ilmu Kesehatan Muhammadiyah Lhokseumawe, 2025)
Sedentary lifestyle can increase the risk of coronary heart disease characterized by lack of physical activity and the length of time spent sitting or lying down. Sedentary lifestyle is a condition of lack of physical activity that can inhibit the risk of coronary heart disease, one way to prevent it is with good self-care, including stress management, healthy eating patterns, and sufficient physical activity. This study aims to explore the relationship between self-care and sedentary lifestyle with the prevalence of coronary heart disease at the dr. Zainoel Abidin Banda Aceh General Hospital. This study uses a descriptive correlative method with a cross-sectional design. The study population of coronary heart disease patients at the dr. Zainoel Abidin Banda Aceh General Hospital using a purposive sampling technique totaling 278 people. Data collection tools using the Self Care Of Coronary Heart Disease Inventory and Sedentary Behavior Questionnaire. Data were analyzed using the Chi-Square test. The results showed that there was a relationship between self-care and sedentary lifestyle with the prevalence of coronary heart disease (p-Value 0.039 <0.05). The importance of promoting self-care and reducing sedentary lifestyle habits as an effort to prevent coronary heart disease.